UCAmI 2018 2018
DOI: 10.3390/proceedings2191212
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Interactive Furniture for Smart Cities

Abstract: The adaptation of cities to a future in which connectivity is at the service of the citizens will be a reality by creating interaction spaces and augmented urban areas. The research on this field falls within the scope of Smart Cities (SC) with the advantages that the common public spaces provide as new points for information exchange between the city, the urban furniture and their citizens. Kiosk systems have been recognized as an appropriate mean for providing event-aware and localized information to the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…We found that many of the features available through solar bus shelters, including Wi-Fi connectivity, information displays and ambient data collection through integrated sensors, are also being applied to a range of other smart infrastructure and services (e.g., [31,32]). Consequently, bus shelters are not the only piece of everyday urban infrastructure that can be made "smarter".…”
Section: Discussionmentioning
confidence: 99%
“…We found that many of the features available through solar bus shelters, including Wi-Fi connectivity, information displays and ambient data collection through integrated sensors, are also being applied to a range of other smart infrastructure and services (e.g., [31,32]). Consequently, bus shelters are not the only piece of everyday urban infrastructure that can be made "smarter".…”
Section: Discussionmentioning
confidence: 99%
“…A project developed at the University of Deusto (Bilbao, Spain) involved an intelligent digital kiosk which featured a series of hardware and software components for sensing different environmental conditions, multimodal interaction with users and for conveying the captured data to the cloud. The custom-based contents visualized to the users were controlled remotely through a specific system for management (Gómez-Carmona et al. , 2018).…”
Section: Initial Classification and Methodologymentioning
confidence: 99%
“…Currently, urban furniture incorporating smart technology is mainstream in urban management. For example, urban furniture with smart systems have been employed as a new platform for information exchange between cities and urban settlements in smart city situations [ 31 ]. Moreover, smart urban furniture with sensors can collect various data describing air quality, traffic and noise of cities, providing useful feedback on city dynamics for policymakers [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, the development of urban furniture tends to follow two main characteristics: one is diversity, while the other is intellectualization [31]. Urban furniture differs from region to region due to the variety of demographic, economic, cultural and lifestyle factors [32].…”
Section: Urban Furniturementioning
confidence: 99%